Two cats to the rescue - Watson, Tom, 1965- (Watson, Tom, 1965- Stick Cat, 2019)
When little Millie wanders off, Stick Cat needs to get her back. It's a rescue mission with too many obstacles to count. There's a runaway butterfly, a pole-vaulting adventure, and a growling beast in the woods. Yikes. And, of course, there's Edith. Oh, Edith. Will Stick Cat be able to navigate around her wacky plans, fragile ego and peculiar ways? Just when he's doubting his chances, five familiar dogs burst onto the scene to help this rescue mission succeed.--